2022
DOI: 10.1139/cjss-2021-0189
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effect of copper and zinc in fertilization of spring wheat under low soil phosphorus conditions

Abstract: Sound micronutrient management requires an understanding of nutrient interactions and transformation processes in soil-plant system which can regulate bioavailability and plant uptake. A series of studies was conducted under controlled environment and field conditions to evaluate wheat response to Cu and Zn fertilization on P deficient soils from western Canada. The grain and straw yields of wheat were reduced in two (Waskada and Tisdale) of three soils used in the controlled environment study, while yield was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Numerous studies have shown that due to P-Zn antagonism, P fertilizer application affects Zn uptake by crop roots and Zn translocation from vegetative organs to grains, thus significantly reducing Zn accumulation in aboveground organs and affecting grain Zn concentrations [26,27,46,47]. A field experiment conducted on calcareous soil showed that long-term P fertilizer application increased grain yield by 15%, but the grain Zn concentration decreased by 6.8-9.2 mg kg −1 per 100 kg P ha −1 application, with P application significantly reducing root mycorrhizal infection rates, thus affecting root Zn uptake [13,48].…”
Section: Grain Zn Concentration and Bioavailability Response To Diffe...mentioning
confidence: 99%
“…Numerous studies have shown that due to P-Zn antagonism, P fertilizer application affects Zn uptake by crop roots and Zn translocation from vegetative organs to grains, thus significantly reducing Zn accumulation in aboveground organs and affecting grain Zn concentrations [26,27,46,47]. A field experiment conducted on calcareous soil showed that long-term P fertilizer application increased grain yield by 15%, but the grain Zn concentration decreased by 6.8-9.2 mg kg −1 per 100 kg P ha −1 application, with P application significantly reducing root mycorrhizal infection rates, thus affecting root Zn uptake [13,48].…”
Section: Grain Zn Concentration and Bioavailability Response To Diffe...mentioning
confidence: 99%